2022
DOI: 10.1155/2022/8529395
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Chinese Herbal Medicine and Recurrence and Metastasis in Patients with Stages II and III Colorectal Cancer: A Cohort Study in China

Abstract: Background. To evaluate the associations between long-term oral Chinese herbal medicines (CHMs) and recurrence and metastasis (R&M) in patients with stage II and III colorectal cancer (CRC). Furthermore, we aimed to determine the correlation between different syndrome patterns and prognosis and summarized the regularities among CHMs prescriptions, providing reference for clinical practice. Methods. An ambispective cohort study was conducted. All CRC patients who sought evaluation and treatment at Xiyuan Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A great quantity of Chinese patients with colon cancer seek help from TCM during or after standard first-line therapy. Prospective cohort studies confirmed that long duration of TCM herbal use was associated with improved disease-free survival outcomes in patients with stage II and III colorectal cancer [ 16 18 ]. A retrospective cohort study indicated that adherence to medication of TCM after surgery could significantly improve disease-free survival in colorectal patients with stage III disease [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A great quantity of Chinese patients with colon cancer seek help from TCM during or after standard first-line therapy. Prospective cohort studies confirmed that long duration of TCM herbal use was associated with improved disease-free survival outcomes in patients with stage II and III colorectal cancer [ 16 18 ]. A retrospective cohort study indicated that adherence to medication of TCM after surgery could significantly improve disease-free survival in colorectal patients with stage III disease [ 19 ].…”
Section: Introductionmentioning
confidence: 99%